Significant improvement of bone mineral density and bone turnover markers by denosumab therapy in bisphosphonate-unresponsive patients. Issue 2 (February 2017) - Kamimura, M.; Nakamura, Y.; Ikegami, S.; Uchiyama, S.; Kato, H.; Taguchi, A.
Abstract Summary Bone mineral density (BMD) sometimes cannot be improved by long-term bisphosphonate (BP) therapy in osteoporosis (OP). This study showed that lumbar as well as hip BMD significantly increased after denosumab treatment in patients not responsive to BPs. Thus, denosumab may be a strong OP treatment option for BP-unresponsive patients. Introduction BMD sometimes cannot be improved by long-term BP therapy. Methods We administered denosumab to osteoporotic patients with a poor response to BPs who had been taking them for 2 years or longer. Ninety-eight women with BP-poor responsive OP were enrolled in this study. Mean (standard deviation [SD]) age was 71.2 (6.9) years and mean (SD) duration of BP treatment was 59.9 (34.3) months. We distinguished BP responders from non-responders based on changes in BMD values at denosumab commencement (baseline) from 2 years beforehand. Results There were no significant differences in age, duration of BP use, bone turnover markers, or BMD at baseline between the groups. Prior to denosumab, BMD had increased significantly in responders and decreased significantly in non-responders. Bone turnover markers had decreased significantly at 4 months of denosumab treatment (P  < 0.001) and lumbar and hip BMD were significantly increased at 1 year of therapy in both groups (P  < 0.001). Simple correlation coefficients were −0.337 for lumbar and −0.339 for hip BMD changes (bothP  = 0.001) before and after denosumab treatment. Both at the lumbar spine and hips, decreased BMD before denosumab therapy was significantly associated with an increase in BMD at 1 year of treatment (spine, t value = −3.502, P  = 0.001, R  = 0.113; hip, t value = −3.526, P  = 0.001, R  = 0.115). Conclusions These results suggest that denosumab may be a strong OP treatment option for BP-unresponsive patients.